Pengaruh Penyuluhan Kesehatan Mengenai Penanganan Scabies Terhadap Masyarakat Kabupaten Takalar Sulawesi Selatan - Idris, Irma Suryani; Suryani, A.Irma; Hiola, St. fatmah (bionature, 2020)
Abstract. Scabies disease or in society better known as scurvy is a parasitic infection of the skin caused by Sarcoptes scabei var hominis. The incidence of scabies in developing countries shows a cycle of fluctuation or increase. The distribution, prevalence, and infection of this parasitic skin disease depend on the area and population studied. This counseling was held in Takalar District with 15 respondents as being school teachers. Outreach results obtained knowledge of the increase in respondents' knowledge. The average proportion of knowledge before counseling was 60.83%, after counseling it increased to 92.22%.Keywords: Scabies, Counseling, Takalar